Manajemen Sumber Daya Manusia (Study Kasus: Sekolah Tinggi Ilmu Tarbiyah Qurrota A’yun) - Rian Hidayat; Sardin A. Anwar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Writing this article aims to determine the role of human resource management in organi-zationsSTIT Qurrota A’yun. The writing of this article uses the method of literature review (library research). From the discussion it can be concluded that Human Resource Man-agement is an element of HRM. Human workforce is not only capable, capable, and skilled, it is also important for their willingness and sincerity to work effectively and efficiently. Employees' abilities and skills are meaningless if they are not followed by work morale and employee discipline in realizing the goals of human resource management having five functions, namely the Procurement Function, Development function, Compensation func-tion, and Maintenance function. functional goals, social goals, personal goals. Human re-source management is needed to improve the effectiveness of human resources in the or-ganization. The goal is to provide the organization with an effective work unit. To achieve this goal, the study of personnel management will show how companies should acquire, develop, use, evaluate, and retain employees in number (quantity) and type (quality).